Transport preferences of the students and employers in Lublin University of Technology - Bis, Jakub; Kojro, Magda (Journal of Computer Sciences Institute, 2020)
The problem of movement is very important in the context of logistic management, which has been gaining importance in recent years with the increasing phenomenon of people moving to large urban agglomerations. The article presents the transport preferences of employees and students the Lublin University of Technology. IT tools were used for the analysis, such as the Analysis ToolPak add-on and PowerMap in Microsoft Excel.